PENGEMBANGAN APLIKASI BUSINESS TO BUSINESS PADA KERAJINAN KAIN PERCA BANYUMAS PRINGSEWU - Kanti Lestari; Kasmi Kasmi; Derga Putra Megantara (Jurnal Signaling, 2020)
Electronic commerce is business activities with the aim of taking advantage, such as sellers, purchases, services, information, and trade through intermediaries, namely through computer networks, especially the internet. The products of Micro, Small and Medium Enterprises in Pringsewu Regency are experiencing development but have various weaknesses including market orientation, quality of human resources, mastery of technology, market access, and capital. To improve performance and speed up and facilitate data processing and information processing for Micro, Small and Medium Enterprises, it is necessary to create an information system for the sale of Micro, Small and Medium Business Products based on the BtoB Application and Website which can simplify the transaction and promotion process as well as ordering stock items by utilizing Website facilities. The design model used by the author in building this application is to use the Rational Unified Process (RUP) design model. With this application, it can support the transaction process and promotion of Micro, Small and Medium Enterprises Products in Pringsewu Regency to be more effective and efficient.